Cone it Down: A Countdown of the Top 10 Cone Beam Breast CT Pearls - Skalski , K.; Melendez , P.; O’connell , A.; ,; ,; , (Seram, 2021)
Background Information: Cone beam breast CT (CBCT) is a dedicated breast imaging system which utilizes cone beam computed tomography to provide true isotropic 3D images of the breast for diagnostic imaging. Currently the only CBCT approved by the FDA is the Koning Breast CT in West Henrietta, NY, approved in 2015. Named cone beam due to the large cone angle x-ray beam that enables the full breast to be imaged in each acquired image. The x-ray tube and detector rotate around the breast and acquire 300 low dose projection images in 10 seconds to create a 3D image of the breast without compression. The purpose of this education exhibit is to highlight the top 10 reasons why CBCT should be considered in conjunction with other imaging modalities in breast imaging. Discussing 10 important pearls of CBCT the learner will be able to compare the standard imaging modalities including mammography, tomosynthesis, ultrasound and MR to CBCT. Multimodality assessment of the cone beam technique ultimately will define the benefits and drawbacks of each imaging modality used in diagnostic breast imaging. Educational Goals/Teaching Points: After participating in this educational presentation, the learner will be familiar with : 1) What cone beam breast CT (CBCT) is and how it works 2) Role of CBCT 3) Comparison of CBCT with standard imaging modality. Key Anatomic/Physiologic Issues and Imaging Findings/Techniques: Discussion points: 1) True 3D images are Obtained 2) No Compression Necessary 3) Iodine Contrast Compatible 4) Biopsy Capable 5) Radiation Comparison and Safety 6) Field of View and Coverage 7) Scanner Time 8) Patient Cultural and Privacy Considerations 9) Risk Based Screening 10) Cancer Detection Paradigm Shift Conclusion: Although breast CT is not a new technique, its use in breast imaging is novel. Multimodality imaging is important to explore in every field of radiology as differences in modalities allow for discovering new ways to diagnose subtle pathology which can help clinicians guide management. After participating in this educational exhibit, the learner will be fully immersed in CBCT imaging understanding how it compares to standard imaging modalities and how pathology is diagnosed using CBCT.